2006
DOI: 10.1037/0021-9010.91.5.1114
|View full text |Cite
|
Sign up to set email alerts
|

A meta-analytic evaluation of the impact of dimension and exercise factors on assessment center ratings.

Abstract: Two recent reviews have attempted to summarize findings quantitatively regarding assessment center (AC) construct-related validity (i.e., Lance, Lambert, Gewin, Lievens, & Conway, 2004; Lievens & Conway, 2001). Unlike these previous studies, which reanalyzed individual multitrait-multimethod (MTMM) matrices from previously published research, the authors recoded and combined past matrices into a single MTMM matrix. This matrix, comprised of 6 dimensions each measured by 6 exercises, was then analyzed, providin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
158
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 102 publications
(168 citation statements)
references
References 33 publications
9
158
1
Order By: Relevance
“…An issue that has been raised in the AC literature is the possibility that there are often conceptual similarities among the different dimensions used in operational ACs (e.g., as implied in Bowler & Woehr, 2006) and this is likely to be true in the present study. If conceptual similarities between different dimensions are apparent, then this has the potential to inflate person main effects.…”
Section: Limitations and Future Directionsmentioning
confidence: 86%
“…An issue that has been raised in the AC literature is the possibility that there are often conceptual similarities among the different dimensions used in operational ACs (e.g., as implied in Bowler & Woehr, 2006) and this is likely to be true in the present study. If conceptual similarities between different dimensions are apparent, then this has the potential to inflate person main effects.…”
Section: Limitations and Future Directionsmentioning
confidence: 86%
“…Whereas results from the Lance, Lambert et al (2004) analysis sided with other individual studies that concluded that assessment center PEDRs are a function of exercises and not dimensions (cf. Bycio et al, 1987;Lance et al, 2000;Lance, Foster, et al, 2004;Lievens& Conway, 2001), Bowler and Woehr (2006) and Lievens and Conway (2001) produced results to contrary. Interestingly, the findings of all of these studies were based on the same statistical technique -a CFA of a MTMM matrix.…”
Section: Bowler and Woehr (2006)mentioning
confidence: 88%
“…Thus, they concluded that exercise effects preside over dimension effects in assessment center PEDRs. Bowler and Woehr (2006) conducted a similar study that also reexamined a similar set of previously reported assessment center MTMM matrices. However, rather than individually reanalyze each MTMM matrix, they chose to recode the data from 35 MTMM matrices into a single MTMM matrix comprised of six dimensions and six exercises.…”
Section: Previous Reviews Of Assessment Center Construct-related Valimentioning
confidence: 99%
See 2 more Smart Citations